The hidden cost of profit sharing on participation in employee stock purchase plans - Jan Christoph Hennig; Rieke Hullmann; Holger A. Rau; Michael Wolff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
Many firms use equity-based profit sharing to boost participation in employee stock purchase plans (ESPPs). Using a large panel data set (N=262,824) of a multinational firm, we compare the reactions of former ESPP participants and non-participants to a profit sharing distribution (PSD). We find a dysfunctional effect. Although many former non-participants sign in, almost a similar share of employees leave the ESPP after the PSD. A closer look highlights the importance of social preferences when all employees enjoy profit sharing. Prosocial former participants show a motivational crowding out effect and leave the program, as the equity norm is violated.
Keywords: D03; J24; J33; J54; M52; 330; Employee Stock Purchase Plans; Gift Exchange; Motivational Crowding Out; NormViolation